Do we need more scientists? - Teitelbaum, Michael S. (Public Interest)
For much of the past 20 years, forecasts of an impending shortage of scientists and engineers in America have gained in popularity. The supposed causes of this dearth are weaknesses in elementary, secondary, or higher education; insufficient financing of the disciplines; declining interest in science and engineering among U.S. students; or some combination of these. Alongside such arguments, and occassionally in the same publications in which they appear, are reports of layoffs of tens of thousands of scientists and engineers in the computer, telecommunications, and aerospace industries, of the profound frustration and even anger felt by new Ph.D.'s unable to find stable employment in traditional science and engineering career paths, and of senior scientists and engineers who are advising undergraduates against pursuing careers in their own fields. The writer examines whether there actually is a shortage of scientists and engineers in the United States.